2017
DOI: 10.1002/ett.3229
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzification supported spectrum decision framework for cognitive radio networks

Abstract: Efficient decision support framework and swift occupation of the available licensed spectrum slot by secondary users (SUs) are the challenging issues in cognitive radio networks. An SU has to sense multiple target frequency spectrum slots in the shortest possible time before deciding to select and occupy the best idle slot for its transmission. A spectrum decision framework for the SUs in cognitive radio networks based on fuzzy logic is proposed. The activity time, possession, and quality of service of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The existing policy of spectrum allocation works on static mode, where the available frequency spectra are divided into subbands. Each subband is exclusively assigned to the specific service provider, known as licensed user or primary user (PU) . However, based on the recent published reports of Federal Communications Commission in USA and few other regulatory bodies, eg, Office of Communications in UK, it is found that major portions of the allocated RF spectra are underutilized by the licensed users .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The existing policy of spectrum allocation works on static mode, where the available frequency spectra are divided into subbands. Each subband is exclusively assigned to the specific service provider, known as licensed user or primary user (PU) . However, based on the recent published reports of Federal Communications Commission in USA and few other regulatory bodies, eg, Office of Communications in UK, it is found that major portions of the allocated RF spectra are underutilized by the licensed users .…”
Section: Introductionmentioning
confidence: 99%
“…Each subband is exclusively assigned to the specific service provider, known as licensed user or primary user (PU) . However, based on the recent published reports of Federal Communications Commission in USA and few other regulatory bodies, eg, Office of Communications in UK, it is found that major portions of the allocated RF spectra are underutilized by the licensed users . Cognitive radio (CR) communication mitigates this spectrum underutilization problem by allowing the CR/secondary users (SUs) either to access the spectrum opportunistically (when PU is not transmitting) or share the same frequency band with PU subject to meeting its tolerable interference .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the frequency spectrum has been saturated due to the coexistence of different technologies and standards, the provision of opportunistic spectrum access for sensors in CRSNs is an important task . In such networks unlicensed cognitive radio users (ie, sensors) or Secondary Users (SUs) can use the frequency spectrum that belongs to some licensed Primary Users (PUs), if they do not cause harmful interference with PUs . The application of CRSNs can be found in the paradigm of Internet of Things (IoT).…”
Section: Introductionmentioning
confidence: 99%